Association of Haptoglobin Phenotypes with Clinical Features of Preterm Labor Disease - Hossein Ali Khazaei; Batoul Teymuri; Alireza Nakhaei; Mehdi Mohammadi; Mehrangeez Noura; Amin Khazaei; Neda Tofiqh; Nima Rezaei (Acta Medica Iranica, 2013)
Preterm birth means the birth before thirty seven week of pregnancy that causes a lot of complications for the baby. Variety factors are suggested to be involved in disease. In this study, we decided to evaluate haptoglobin (Hp) phenotypes association with clinical features of patients suffered from premature delivery to understand better the possible correlation of genetic and clinical features in this disease. This cross sectional analytic descriptive study has been carried out in two groups of 120 women, 60 with preterm and 60 with term labor. Patients were selected with previously diagnosed by a gynecologist with preterm birth in hospital during the study period. After performing diagnostic tests, the frequency of each haptoglobin phenotype in the two groups was analyzed using the X2 test and SPSS software. The maximum serum haptoglobin phenotype frequency in patients with Hp2-2, was 43 (71.7%) whereas in healthy individuals, 35 (58.3%). No statistically significant differences between the two groups was found (P=0.310). But based on some patients clinical features such as their history of preterm delivery, previous history of recurrent abortions and history of preterm delivery in their family, significant association was found with Hp2-2 compared with healthy control (P<0.003). This study showed that Hp2-2 phenotypes levels in the case group was higher than in control but the factors influencing the presence or absence of preterm labor is clinically various.